Effect of First Trough Vancomycin Concentration on the Occurrence of AKI in Critically Ill Patients: A Retrospective Study of the MIMIC-IV Database - Li, Longzhu; Zhang, Luming; Li, Shaojin; Xu, Fengshuo; Li, Li; Li, Shuna; Lyu, Jun; Yin, Haiyan (Frontiers in Medicine, 2022)
Abstract Background: Vancomycin can effectively inhibit Gram-positive cocci and is widely used in critically ill patients. This study utilized a large public database to explore the effect of patients’ first vancomycin trough concentration (FVTC) on the occurrence of acute kidney injury (AKI) and mortality after receiving vancomycin treatment in intensive care unit (ICU). Methods: Critically ill patients who used vancomycin in the Medical Information Mart for Intensive Care (MIMIC) IV have been retrospectively studied. The outcomes included the occurrence of AKI during the use of vancomycin or within 72 h of withdrawal, ICU mortality and hospital mortality. Restricted cubic splines (RCS) were used to analyze the linear relationship between FVTC and the outcomes. Multivariate logistic/Cox regression analysis was used to analyze the association between patient’s FVTC and the occurrence of AKI, ICU mortality, and in-hospital mortality. Results: The study ultimately included 3,917 patients from the MIMIC-IV database who had been treated with vancomycin for more than 48 hours. First of all, the RCS proved the linear relationship between FVTC and the outcomes. After controlling for all covariates as confounders in logistic/Cox regression, FVTC was a risk factor with the occurrence of AKI (OR: 1.02; 95%CI:1.01–1.04), ICU mortality (HR:1.02; 95%CI:1.01–1.03), and in-hospital mortality (HR:1.02; 95%CI:1.01–1.03). Moreover, patients were divided into four groups in the light of the FVTC value: group1 ≤ 10 mg/L, 10 20 mg/L. Categorical variables indicated that group 3 and group 4 had a significant relationship on the occurrence of AKI [group 3: (OR:1.36; 95%CI: 1.02–1.81); group 4: (OR: 1.76; 95%CI: 1.32–2.35)] and ICU mortality [group 3: (HR: 1.47; 95%CI: 1.03–2.09); group 4: (HR: 1.87; 95%CI: 1.33–2.62)], compared to group 1, while group 4 had a significant effect on in-hospital mortality (HR: 1.48; 95%CI: 1.15–1.91). Conclusions: FVTC is associated with the occurrence of AKI and increased ICU and in-hospital mortality in critically ill patients. Therefore, in clinical practice, patients in intensive care settings receiving vancomycin should be closely monitored for FVTC to prevent drug-related nephrotoxicity and reduce patient mortality.